The therapeutic potential of stem cells in umbilical cord and umbilical cord blood - Watt, S; Su, C; Chan, J (2010)
Haemopoietic stem cell transplantation (HSCT) is a curative therapy for severe haematological disorders. It was fi rst carried out successfully ~50 years ago. With technological advances, HSCT has expanded rapidly over the past 20 years. 1,2 Current indications for HSCT include leukaemias, lymphomas, solid tumours (e.g. neuroblastomas), severe combined immunodefi ciencies, inborn errors of metabolism, autoimmune diseases and severe anaemias. 1-3 HSCT is now provided to ~70,000 patients p.a. worldwide. In the UK, approximately 3,000 HSC transplants are performed p.a. (www.bsbmt.com), contributing to ~25,000 p.a. across Europe. 1-4 Of those HSCT provided worldwide, ~70-80% have autologous or related allogeneic HSCT. The remainder have unrelated HSCT, of which almost 20% are sourced from unrelated umbilical cord blood (UCB) donations in the USA and 50% in Japan. 4 Despite significant advances, overall survival following HSCT can vary because of disease relapse, engraftment failure, infections and Graft versus Host Disease (GvHD). 5,6 In this review, we describe the current use, advantages and limitations of UCB for HSCT, principally concentrating on unrelated allogeneic UCB units. However, UCB and the umbilical cord (UC) also contain other stem/progenitor cells (e.g. mesenchymal stem cells (MSC)) and hence we extend our discussions to these describing their potential therapeutic use in HSCT and regenerative medicine. © 2010 JMS.